Effect of plant diversity and drought on the agronomic performance of intensively managed grassland communities - Grange, Guylain (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Statistics, 2022)
Temperate agro-ecosystems are crucial for food production and financially important for the rural economy, but can have strong environmental impacts and are threatened by increased frequency of extreme weather events. Over the last decades, research showed that plant diversity can enhance ecosystem productivity and resilience in temperate agro-ecosystems. However, consistent knowledge gaps remain in the characterization of the biodiversity ? ecosystem functioning relationship (BEF). In particular, more work is needed on the potential transfer of ecological principles about BEF relationship to intensively managed agro-ecosystems. Better knowledge of the effect of plant diversity on field scale productivity, resilience and ecosystem services could help to enhance agronomic and environmental performances of intensive agro-ecosystems. To investigate the effect of plant diversity on ecosystem functioning, I carried out a grassland experiment in Wexford, Ireland. The field was sown using a six-species pool from three functional groups: grass (Lolium perenne and Phleum pratense), legume (Trifolium pratense and Trifolium repens) and herb (Cichorium intybus and Plantago lanceolata). Plant diversity was manipulated using a simplex design to form 19 communities of one to six species, that were established across a total of 39 plots, all receiving an annual fertiliser rate of 150 kg N ha-1 yr-1 (150N). Four extra replicates of L. perenne receiving double nitrogen fertiliser were added (300N). Each plot was randomly subdivided in two different water supply treatments: one subplot was a control (rainfed), and a two-month summer drought was simulated on the other (drought). Subplots were harvested seven times each year for two years. Grassland cover was then terminated to establish a model crop, keeping the same field layout. No drought was applied, and all plots received 40N, including the former 300N plots. Four crop harvests were performed to measure the legacy effect of the previous grassland treatments. A series of analyses were carried out on the data from across the three years of data using Diversity-Interactions modelling to relate ecosystem functions to plant diversity (including species identities and interactions) and climatic conditions (water supply). Biomass yield in the grassland phase of the rotation was strongly influenced by plant diversity. Interactions between functional groups enhanced annual biomass production to the point that a wide range of mixtures outperformed the best monoculture (i.e. transgressive overyielding). Interactions were maintained under drought conditions. I compared the 300N L. perenne monoculture (low-diversity, high-input) to the 150N equi-proportional six-species mixture (high-diversity, low-input). Even when stressed by drought, the high-diversity, low-input mixture outperformed the rainfed low-diversity, high-input comparison. No evidence of grassland species interactions were found on the legacy effect, but strong dissimilarities were observed among species. Higher legume proportion in grassland led to higher legacy effect. The lowest legacy effect was from the 300N L. perenne monoculture. Due to the absence of interspecific interactions on legacy effect, no overyielding was observed in the crop phase of the rotation. Drought applied in the grassland phase had a constant effect on legacy, reducing crop yield by the same magnitude across all plots. Considering the two phases of the grassland-crop rotation, selection of the ?best? grassland community depends on the relative importance of each phase of the rotation. High diversity favoured grassland phase yield, while high legume content stimulated the yield of a follow-on crop receiving 40N. A diverse grassland mixture including a high proportion of legume would deliver high performances in both phases. To upscale the analysis of the BEF relationship, I investigated multiple ecosystem functions that reflect the multiple purposes of intensive agro-ecosystems. The effects of diversity on dry matter yield, legacy effect, nitrogen fertiliser efficiency, yield consistency, forage digestibility and weed suppression were simultaneously assessed in a multifunctionality analysis. To do so, a multivariate model was combined with the Diversity-Interactions approach. The effect of plant diversity was function-specific. Species interactions were strong and positive for half of the functions, and neutral for the others, with the overall effect of diversity remaining positive. The benefit of interactions added to divergent species identity effects across functional groups resulted in species rich balanced mixtures achieving the highest performance averaged across functions. The low-diversity, high-input comparison was amongst the lowest performing communities. Again, the effect of drought was either constant or applied only to species identities, depending on the function. Across functions, balanced mixtures of grass, legume and herb outperformed both the best monocultures and the low-diversity, high-input comparison, while mitigating the effects of an extreme summer drought. This thesis demonstrates that averaged across functions, interactions were strong enough for a wide range of mixtures to achieve transgressive over-performance under intensive management, even when a summer drought occurs. Although species interactions were not significant for all functions, no negative interaction effect was noted and the net effect of species interactions was positive. Drought did not affect the strength of plant interaction effects averaged across functions, resulting in a relatively higher benefit of diversity when species identity effects were reduced by drought stress. Positive interactions, even under drought conditions, add to the overall benefit of plant diversity in intensively managed agro-ecosystems, in contrast with increased fertiliser that showed poor performances across most of the functions studied. In conclusion, I show that mixing plant species is a practical way of enhancing the performances of intensively managed agro-ecosystems in several ways across a crop rotation, while mitigating the effect of a weather disturbance. Intensification based on ecological principles proved to be more efficient than increased fertiliser use on most of the aspects studied. Multi-species systems are thus a promising tool to reduce the reliance on fertiliser inputs and to help protect against extreme weather conditions.
APPROVED
Keywords: Drought; Multi-species; Grassland; Intensive; Multifunctionality; Legacy; Transgressive overyielding